PENGARUH PROGRAM PEMBERDAYAAN MASYARAKAT TERHADAP PENGELUARAN KONSUMSI RUMAH TANGGA DI PROVINSI PAPUA - I Wayan Sukadana, Richardo Bano (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Uneven household consumption expenditure still leaves problems that must be faced in the development of an area. Papua Province consisting of 29 districts / cities has a background of differences between regions. Such differences can be an obstacle in economic equality in each region and will have an impact on household consumption expenditures. The purpose of this research is to determine the influence of infrastructure empowerment programs, economic empowerment programs, and social empowerment programs on household consumption expenditures. This research was conducted in every district / city in papua province. Data used from 2016 – 2017. Data analysis techniques used are descriptive analysis techniques and multiple linear regression analysis. Based on the results of the analysis found simultaneously infrastructure empowerment programs, economic empowerment and social empowerment simultaneously have no real and significant influence on household consumption expenditures. This also has an impact on the high level of poverty on Papuan soil, based on the results of the analysis found that these programs do not have a significant influence on poverty in Papua. Keywords: infrastructure empowerment programs, economic empowerment programs, social empowerment programs, household consumption expenditures